(untitled) (Journal of the College of Basic Education, 2024)
This study sought to explain the most important social repercussions of the Corona pandemic on Iraqi society. We have shown the social repercussions that this pandemic has had and will have on the individual, the family, and Iraqi society, and how the pandemic has affected relationships and behaviors. Many social customs and behaviors have changed, such as the customs of shaking hands and kissing. Likewise, Visits between relatives and friends decreased, and marriage, funeral, and burial ceremonies changed. We also explained the role of the Iraqi family during the pandemic and what jobs it returned to after it had lost before this crisis, and what is the impact of the pandemic on its cohesion, and what are the reasons that led to an increase in cases of divorce and domestic violence during the pandemic? The study also sought to explain the effects of the pandemic on the education sector, this important sector, which is considered one of the most important sectors in society, and how it affected the education of millions of students at all levels of education. We took the city of Baghdad as a model for the study. This study is divided into two chapters: The first chapter, which consists of two sections, deals with the problem, importance, and objectives of the study, and the most important concepts related to it. The second chapter, which consists of three sections, in which the first section deals with the methodology of the study. The second section contains the field study, and some The social repercussions of the Corona pandemic, and the third section: results and recommendations.